Antimicrobial Activity of the Most Common Antibiotic-Releasing Systems Employed in Current Orthopedic Surgery: in vitro Study - Štícha, Roman; Fulín, Petr; Nyč, Otakar; Gajdošová, Veronika; Pokorný, David; Šlouf, Miroslav (Acta chirurgiae orthopaedicae et traumatologiae Čechoslovaca, 2023)
PURPOSE OF THE STUDY Infections of joint replacements represent one of the most serious problems in contemporary orthopedics. The joint infections treatment is usually multimodal and involves various combinations of drug delivery and surgical procedures. The aim of this study was to evaluate and compare the bacteriostatic and bactericidal properties of the most common antibiotic carriers used in orthopedic surgery: bone cements mixed with antibiotic and porous calcium sulfate mixed with antibiotic. MATERIAL AND METHODS Three commercial bone cements (Palacos®, Palacos® R+G, Vancogenx®) and commercial porous sulfate (Stimulan®) were prepared with a known concentration of vancomycin (a glycopeptide antibiotic). Specifically, for the purpose of our study, the testing specimens were prepared to release 0, 1, 2, 4, 8, 16, 32, 64, 128, 256, and 512 mg of vancomycin into 1 liter of solution. The specimens with increasing amount of antibiotic were placed in a separate tubes containing 5 mL of Mueller-Hinton broth inoculated with a suspension (0.1 m, McFarland 1) of the reference strain CCM 4223 Staphylococcus aureus to evaluate their bacteriostatic properties (broth dilution method). After this initial incubation and evaluation of the broth dilution method, an inoculum from each tube was transferred onto blood agar plates. After another 24-hour incubation under the same conditions, we evaluated the bactericidal properties (agar plate method). As many as 132 of independent experiments were performed (4 specimens × 11 concentrations × 3 repetitions = 132). RESULTS The bacteriostatic properties of all investigated samples were excellent, perhaps with the exception of the first bone cement (Palacos®). The sample Palacos® started to exhibit bacteriostatic properties at concentrations ≥ 8 mg/mL, while all other samples (Palacos R+G®, Vancogenx®, and Stimulan®) were bacteriostatic in the whole concentration range starting from 1 mg/mL. The bacteriocidic properties did not show such clear trends, but correlated quite well with different properties of the investigated samples during mixing - the most homogeneous samples seemed to exhibit the best and the most reproducible results. DISCUSSION The reliable and reproducible comparison of ATB carriers is a difficult task. The situation is complicated by high numbers of local antibiotic carriers on the market, numerous antibiotics used, and differences in clinical trials at different laboratories. Simple in vitro testing of bacteriostatic and bacteriocidic properties represents a simple and efficient approach to the problem. CONCLUSIONS The study confirmed that the two most common commercial systems used in the orthopedic surgery (bone cements and porous calcium sulfate) prevent bacterial growth (bacteriostatic effect), but they may not be 100% efficient in complete elimination of bacteria (bacteriocidic effect). The scattered results in the case of bacteriocidic tests seemed to be connected with the homogeneity of ATB dispersion in the systems and with the lower reproducibility of the employed agar plate method. Key words: local release of antibiotics; bone cements; calcium sulfate; antimicrobial susceptibility.
Keywords: ortopedie; vankomycin; Orthopedics; Humans; agar; síran vápenatý; lidé; antibakteriální látky; Vancomycin; reprodukovatelnost výsledků; kostní cementy; ortopedické výkony; Anti-Bacterial Agents; Reproducibility of Results; polymethylmethakrylát; Bone Cements; Orthopedic Procedures; Polymethyl Methacrylate; Calcium Sulfate; Agar